Hepatitis C virus infection and risk of pancreatic cancer: A meta-analysis. (April 2020) - Arafa, Ahmed; Eshak, Ehab S.; Abdel Rahman, Tarek A.; Anwar, Manal M.
Highlights: This meta-analysis showed that HCV infection was associated with an increased risk of pancreatic cancer. Adjusting for diabetes, alcohol intake, and smoking attenuated the association. Future population-based prospective cohort studies are highly recommended. Abstract: Background: A growing body of evidence has suggested an association between Hepatitis C virus (HCV) infection and risk of pancreatic cancer (PAC). Herein, we conducted a meta-analysis of available evidence to explore this association. Methods: We systematically retrieved studies that investigated the association between HCV infection and risk of PAC. Pooled odds ratio (OR) with corresponding 95 % confidence interval (CI) of PAC for patients with HCV infection was calculated using the fixed- or random-effects model. Results: A total of 16 studies (8 cohort and 8 case-control) were included in this meta-analysis. Combined, patients with HCV infection were more likely to develop PAC than people without it (pooled OR = 1.51, 95 % CI: 1.31, 1.74; I 2 = 63.49 %, p-value for heterogeneity< 0.001). Studies that adjusted their results for diabetes, chronic pancreatitis, alcohol intake, and smoking showed lower ORs than studies that did not adjust for them. Conclusion: HCV infection was associated with increased risk of PAC, but this association was attenuated among studies that adjusted their results for potential risk factors for PAC. Future prospective cohort studies are needed to confirm this association.